A comprehensive genome‐wide analysis of melanoma Breslow thickness identifies interaction between CDC42 and SCIN genetic variants. Issue 9 (23rd July 2016) - Vaysse, Amaury; Fang, Shenying; Brossard, Myriam; Wei, Qingyi; Chen, Wei V.; Mohamdi, Hamida; Vincent‐Fetita, Lynda; Margaritte‐Jeannin, Patricia; Lavielle, Nolwenn; Maubec, Eve; Lathrop, Mark; Avril, Marie‐Françoise; et al.
Abstract : Breslow thickness (BT) is a major prognostic factor of cutaneous melanoma (CM), the most fatal skin cancer. The genetic component of BT has only been explored by candidate gene studies with inconsistent results. Our objective was to uncover the genetic factors underlying BT using an hypothesis‐free genome‐wide approach. Our analysis strategy integrated a genome‐wide association study (GWAS) of single nucleotide polymorphisms (SNPs) for BT followed by pathway analysis of GWAS outcomes using the gene‐set enrichment analysis (GSEA) method and epistasis analysis within BT‐associated pathways. This strategy was applied to two large CM datasets with Hapmap3‐imputed SNP data: the French MELARISK study for discovery (966 cases) and the MD Anderson Cancer Center study (1, 546 cases) for replication. While no marginal effect of individual SNPs was revealed through GWAS, three pathways, defined by gene ontology (GO) categories were significantly enriched in genes associated with BT (false discovery rate ≤5% in both studies): hormone activity, cytokine activity and myeloid cell differentiation. Epistasis analysis, within each significant GO, identified a statistically significant interaction between CDC42 and SCIN SNPs ( p meta‐int =2.2 × 10 −6, which met the overall multiple‐testing corrected threshold of 2.5 × 10 −6 ). These two SNPs (and proxies) are strongly associated with CDC42 and SCIN gene expression levels and map to regulatory elements in skin cells. This interaction has important biological relevance since CDC42 and SCIN proteins have opposite effects in actin cytoskeleton organization and dynamics, a key mechanism underlying melanoma cell migration and invasion. Abstract : What's New? A new genetic study evaluates the interactions between genes that may influence melanoma progression. One important prognostic indicator is tumor thickness—patients with thicker tumors have a poorer prognosis. The authors sought genetic factors linked to melanoma thickness. They conducted a genome‐wide association study, followed by a combined pathway and epistasis analysis. They uncovered two genes ( CDC42 and SCIN ) that could work together to influence melanoma thickness. Both are biologically relevant, as they affect cytoskeleton organization and dynamics, mechanisms that play a key role in cell invasion.